Understanding urban land leasing system as a strategic value capture instrument to enhance urban revenue in Ethiopia: A case study of Bahir Dar city - Seid Hussen Yimam; Hans Lind; Belachew Yirsaw Alemu (Economies, 2022)
Since 1993, the Ethiopian government has been using the urban land leasing system to monetize the increase in land value created due to factors other than private investment. Thus, this paper aims to explore and understand whether Bahir Dar city is leveraging the urban land lease system as a strategic value capture instrument to enhance its local revenue or not. This study has used the qualitative research method and in-depth analysis. It has used a desk review of documents and key informant interviews of experts and brokers to collect the data required to realize the objective of this study. The study has found that the majority of the urban land is held in a permit system, with landholders paying a small amount of land rent per annum. In addition, the study has uncovered that the city has transferred most of its land through administrative allotment at low and outdated benchmark prices, which has dwindled its lease revenue. Moreover, it has identified that there is weak enforcement of the lease payment collection, and it has adversely affected the city's urban revenue generation potential. As a result, the city is not leveraging the public land leasing system as a strategic value capture instrument. Based on these findings, this paper has advised the government to implement a modern property tax system to capture value increment on permit holding land. In addition, the study proposes to carry out an empirical investigation and identify the factors that significantly affect the benchmark prices and update the benchmark price regularly given those factors. Moreover, the study has suggested a proper enforcement of the lease payment collection in the city.
Keywords: 330; land lease payment; land lease tender price; lease benchmark price; urban land lease; urban revenue; value capture